2019
DOI: 10.1186/s12885-019-5308-y
|View full text |Cite
|
Sign up to set email alerts
|

Crosslink between Temozolomide and PD-L1 immune-checkpoint inhibition in glioblastoma multiforme

Abstract: BackgroundIn recent years, PD-1/PD-L1 immune checkpoint inhibitors have improved cancer therapy in many tumor types, but no benefit of immune checkpoint therapy has been found in glioblastoma multiforme (GBM). Based on the results of our earlier work, which showed a reduction of PD-L1 expression in patients treated with temozolomide (TMZ), we aimed to investigate the link between TMZ therapy and the immune control point target PD-L1.MethodsRNA-sequencing data from de-novo and recurrent glioblastoma were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 37 publications
0
37
0
1
Order By: Relevance
“…Despite the notable strides forward in immunotherapy as a whole and seemingly promising results in preclinical studies, clinical data have not yet yielded significant improvements in GBM therapy, as most studies reported significant effects in only a select few individuals. [17][18][19][20] This dissonance indicates potential deficiencies in clinical models, as the differing immune systems of mice and humans may distort reliable predictability between preclinical and clinical results. This issue could be partially resolved by means of better animal models or by further advancing personalized drug-screening and treatment options for GBM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the notable strides forward in immunotherapy as a whole and seemingly promising results in preclinical studies, clinical data have not yet yielded significant improvements in GBM therapy, as most studies reported significant effects in only a select few individuals. [17][18][19][20] This dissonance indicates potential deficiencies in clinical models, as the differing immune systems of mice and humans may distort reliable predictability between preclinical and clinical results. This issue could be partially resolved by means of better animal models or by further advancing personalized drug-screening and treatment options for GBM patients.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that a different study found that concurrent TMZ treatment may actually serve to reduce the efficacy of PD-L1 inhibitors, as TMZ treatment leads to a down-regulation of PD-L1 expression in GBM cells, thus diminishing the target of PD-L1 inhibition. [17] Another study demonstrated administration of PD-L1 antibody combined with CTLA-4 antibody (37% survival) produced greater effects than CTLA-4 antibody alone (20% survival). Furthermore, dual checkpoint inhibition in addition to administration of G47∆-mIL12 resulted in even more long-term survivors (89% survival) in mice glioma models.…”
Section: Pd-1 Inhibiting Drugs: Pembrolizumab and Nivolumabmentioning
confidence: 99%
“…Так, иринотекан модулирует иммунное микроокружение путем снижения Foxp3-позитивных регуляторных Т-клеток (Tregклетки) и миелоидных клеток-супрессоров и приводит к увеличению пролиферации продуцирующих интерферон-гамма опухоль-специфических CD8 + -T-клеток [59]. Низкие дозы темозоломида также снижают количество Treg-клеток [60]. Показана возможность проведения GD2-направленной терапии с различными химиопрепаратами.…”
Section: таблицаunclassified
“…Thus far, these trials have largely failed to impact survival in GBM patients, but they have successfully drawn attention to the potent local and systemic immune suppression elicited by GBM [2][3][4][5][6] . In seeking to develop better immune therapies for GBM, many have logically sought to understand how standard-of-care chemotherapy [7][8][9][10] and radiation 11-13 impact the immune system and the tumor immune microenvironment. Although neoadjuvant immunotherapy prior to surgical resection may lead to more effective treatment responses 14 , the impact of standard surgical resection and steroid treatment otherwise remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%